2017
DOI: 10.1039/c7dt03403b
|View full text |Cite|
|
Sign up to set email alerts
|

C–H nickellation of phenol-derived phosphinites: regioselectivity and structures of cyclonickellated complexes

Abstract: This report describes the results of a study on the ortho-C-H nickellation of the aryl phosphinites i-PrP(OAr) derived from the following four groups of substituted phenols: 3-R-CHOH (R = F (b), Me (c), MeO (d), Cl (e)); 3,5-R-CHOH (R = F (f), Me (g), Cl (h), OMe (i)); 2-R-CHOH (R = Me (j), Ph(k)); and 2,6-R-CHOH (R = Me (l), Ph (m)). No nickellation was observed with the phosphinites derived from the 3,5-disubstituted phenols g and h, and the 2,6-disubstituted phenols l and m; in all other cases nickellation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 50 publications
0
23
1
Order By: Relevance
“…While this type of catalyst deactivation is well known with Pd for ligands without 2,6substituted B-rings, for the C-H activation to occur with Ni rapidly, under such mild conditions, and with a non-chelating ligand is remarkable. [49][50][51][52][53][54][55][56][57] It is also notable that this cyclometalation occurs significantly faster than in the analagous CyJohnPhos/Pd system reported by Fink. 15 Computationally, we were unable to locate a reasonable transition state from ii, the L2Ni(II) structure, or the µ-Cl dimer that would lead to 5.…”
Section: Scheme 1 Ni-catalyzed Smc Reaction Ibmentioning
confidence: 60%
“…While this type of catalyst deactivation is well known with Pd for ligands without 2,6substituted B-rings, for the C-H activation to occur with Ni rapidly, under such mild conditions, and with a non-chelating ligand is remarkable. [49][50][51][52][53][54][55][56][57] It is also notable that this cyclometalation occurs significantly faster than in the analagous CyJohnPhos/Pd system reported by Fink. 15 Computationally, we were unable to locate a reasonable transition state from ii, the L2Ni(II) structure, or the µ-Cl dimer that would lead to 5.…”
Section: Scheme 1 Ni-catalyzed Smc Reaction Ibmentioning
confidence: 60%
“…We conclude, therefore, that the zwitterionic species α and β give more accurate descriptions of this complex. The 1 H and 13 C NMR spectra of 3 (Figures S29−S41) indicate that the α form shown in Scheme 5 and featuring a nickellacyclopropane moiety is the prevalent resonance structure of compound 3 in solution. Thus, the two C−H moieties bound to the metal center gave signals in the aliphatic region: δ 1 H at 2.04 and 2.95 ppm; δ 13 C at 18.63 and 37.17 ppm.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This study began by preparation of the target substrate 1 and examination of its reactivity under the conditions used for our previous nickellation studies. , Thus, 1 was treated in acetonitrile with {( i -PrCN)­NiBr 2 } n and Et 3 N (molar ratio of 1.0:1.2:1.2), and the reaction progress was monitored by NMR spectroscopy. 31 P NMR spectral analysis of the greenish mixture obtained after 2 h of stirring at room temperature showed that the initial signal for 1 had been replaced almost completely by two new 31 P resonances at 103 and 202 ppm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations